A reforma agrária no Governo Dilma - Silva, Iris Karine dos Santos (2017)
The present work had as objective the "analysis of the agrarian reform in the first Dilma Government (2011-2014)". The research was guided by historical-dialectical materialism, considering its potential contribution to unveil the reality of the phenomena under study and was an exploratory study, with the purpose of developing and modifying concepts and ideas, in order to elicit elements for work Later. As research procedures, we resorted, on the one hand, to the bibliographic review of the literature found and, on the other hand, to documentary research in institutional sites. The study set out to investigate agrarian reform in the bosom of Brazilian capitalism, with a view to discussing government priorities in directing agrarian policy in the period under analysis. It presents the contextualization about the persistence of latifundia in Brazilian capitalism and its functionality for the constitution of the dominant classes, highlighting how this is incorporated into the new dynamics of capital accumulation. It also addresses the discussion of agrarian reform in the face of the modernization of agriculture and financial capitalism discussing its place within the governmental priorities of agricultural development policy. Finally, we analyze the agrarian reform actions developed in the Dilma government, focusing on the number of settlements created and their impacts on the current land structure. In general, the results show that the agrarian reform in the period studied was lateralized by the subsidy to agribusiness, while it was replaced by compensatory bias policies and by the incentive to existing settlements. Thus, all PT governments and the Dilma government differ only from previous governments in this regard, even with the full expectation of social movements. Another element that stands out is the role of the judiciary in not completing the expropriation proceedings. These issues reflect the actions of the land-based ruling class to maintain their interests. In the face of this situation, agrarian reform has become increasingly a historical struggle and demands, above all, greater efforts from the group of organized workers for its realization.